Corpus insights into the harmonization of commercial media in China: News coverage of migrant worker issues as a case study. (June 2021) - Liu, Eric (Yin); Leung, Janny H.C.
Abstract: Literature abounds regarding media censorship in China, but relatively few studies show how this is linguistically realized, and what impact it has on Chinese media discourse. Using news coverage of migrant worker issues as a lens, this paper demonstrates convergence in reportage between commercial media and state media in China that took place in the last few years. Our corpus-based critical discourse analyses show that negative words/phrases about migrant workers' miseries (e.g., discrimination, physical assault, etc.) have decreased significantly in commercial reportage while positive words/phrases that praise the government's achievements and actions in dealing with migrant worker issues (e.g., the increased income, the active entrepreneurial policy for migrant workers, etc.) have increased remarkably. We also note more shared vocabulary between the reportage of commercial and state media, which reflects a convergence in their reporting style. We attribute such changes to the political ideology of harmony that exerts sweeping influences on Chinese society, and raise concerns about the health of the media landscape in China.